Clinical and biological factors associated with irreversible airway obstruction in adult asthma. (December 2020) - Graff, Sophie; Bricmont, Noëmie; Moermans, Catherine; Henket, Monique; Paulus, Virginie; Guissard, Françoise; Louis, Renaud; Schleich, Florence
Abstract: Background and objective: Airway remodeling, as many other factors, may lead to lung function decline and irreversible airflow obstruction (IRAO) in asthma. This study was undertaken in order to highlight predictors of incomplete reversibility of airflow obstruction in adult asthmatics to identify patients with poorer prognosis and improve their care, and decrease morbidity. Methods: A retrospective study was conducted in 973 asthmatics recruited from the University Asthma Clinic of Liege. Patients with IRAO (post-BD FEV1 /FVC<0.7 & FEV1 <80% predicted) were compared to patients with reversible airway obstruction (RAO) (post-BD FEV1 /FVC≥0.7 & FEV1 ≥80% predicted). TGF-β was measured in sputum supernatant of 85 patients. Results: Seventeen percent of asthmatics presented with IRAO. These patients were significantly older, more smokers, with a lower proportion of female, a longer disease duration, were more poorly controlled with a lower quality of life. This sub-population of asthmatics also showed more often elevated blood and sputum eosinophils and neutrophils, and higher exacerbation and hospitalisation rates in the previous year. The multivariable analysis revealed male gender, longer disease duration, cigarette smoking, ACQ score, sputum eosinophils and neutrophils, ICS dose and OCS maintenance, BMI, and asthma onset as variables independently linked to IRAO. Total TGF-β levels appeared higher in patients with IRAO (n = 38) compared to patients with RAO (n = 47). Conclusion: These data show that risk factors for IRAO are male gender, smoking, a longer disease duration, uncontrolled asthma, eosinophilic or neutrophilic airway inflammation, lower BMI, and later asthma onset. Moreover, TGF-β levels are higher in IRAO. Highlights: Many independent factors can predict irreversible airway obstruction in asthma. Asthma control score is a useful indicator of irreversible airway obstruction. Sputum eosinophils are biomarkers for remodeling as they reflect local inflammation. TGF-β levels are higher in patients with irreversible airway obstruction.